2009
DOI: 10.1371/journal.pone.0005391
|View full text |Cite|
|
Sign up to set email alerts
|

Peptide Bβ15-42 Preserves Endothelial Barrier Function in Shock

Abstract: Loss of vascular barrier function causes leak of fluid and proteins into tissues, extensive leak leads to shock and death. Barriers are largely formed by endothelial cell-cell contacts built up by VE-cadherin and are under the control of RhoGTPases. Here we show that a natural plasmin digest product of fibrin, peptide Bß15-42 (also called FX06), significantly reduces vascular leak and mortality in animal models for Dengue shock syndrome. The ability of Bß15-42 to preserve endothelial barriers is confirmed in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
101
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 49 publications
5
101
0
1
Order By: Relevance
“…14 Fyn interaction with p190RhoGAP leads to the inactivation of RhoA, causing better preservation of endothelial barrier function. 14 In our experiments, B␤ treatment reduced the upregulation of the endothelial adhesion receptors ICAM-1, VCAM-1, and E-selectin, pointing to a possible link to RhoA, which is a known inducer of these adhesion molecules. 25,26 In addition to these anti-inflammatory and vasculoprotective effects, we found that B␤ 15-42 treatment was associated with a significantly better preservation of tubular epithelial integrity and reduced epithelial apoptosis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…14 Fyn interaction with p190RhoGAP leads to the inactivation of RhoA, causing better preservation of endothelial barrier function. 14 In our experiments, B␤ treatment reduced the upregulation of the endothelial adhesion receptors ICAM-1, VCAM-1, and E-selectin, pointing to a possible link to RhoA, which is a known inducer of these adhesion molecules. 25,26 In addition to these anti-inflammatory and vasculoprotective effects, we found that B␤ 15-42 treatment was associated with a significantly better preservation of tubular epithelial integrity and reduced epithelial apoptosis.…”
Section: Discussionsupporting
confidence: 57%
“…16 -19 Additionally, B␤ binding to VE-cadherin was shown to prevent stress-induced RhoA activation in a Fyn-dependent manner, leading to endothelial stabilization and preservation of the endothelial barrier. 14 These anti-inflammatory and vasculoprotective effects of B␤ prompted us to test its therapeutic potential in renal transplantation and allograft rejection.…”
mentioning
confidence: 99%
“…The safety and effi cacy of FX06 in the treatment of vascular leak syndrome has previously been explored in animal models of lipopolysaccharideinduced and dengue haemorrhagic shock. 17 The substance was well tolerated in a phase 2 clinical trial in patients with ST-elevation myocardial infarction. 18 In our patient, we noted no signs of tolerability problems or compromised safety.…”
Section: Discussionmentioning
confidence: 99%
“…Bβ15-42 prevented Rho-kinase activation by dissociating Fyn from VE-cadherin, which in turn associates to p190RhoGAP. Bβ15-42-treated animals had improved survival rates and reduced hemoconcentration and fibrinogen consumption (70). In a cardiac transplant model, Bβ15-42 also attenuated the ischemia-reperfusion injury (71).…”
Section: Fibrin Fragmentsmentioning
confidence: 94%
“…Moreover, Bβ15-42 functions as a signaling molecule. In two different shock models-Dengue shock syndrome and LPS-induced shock model, Bβ15-42 preserved endothelial barrier function by inhibiting stress-induced opening of EC adherens junctions (70). Cell-to-cell contact between ECs is formed Fibrinogen is converted to fibrin, which in turn is degraded by plasmin.…”
Section: Fibrin Fragmentsmentioning
confidence: 99%